Electroactive ion exchange materials: current status in synthesis, applications and future prospects. Issue 17 (6th April 2016) - Du, Xiao; Hao, Xiaogang; Wang, Zhongde; Guan, Guoqing
Abstract : The recent state of and challenges for the synthesis of electroactive ion exchange materials and their application in selective ion separation, supercapacitors and electrochemical ion sensors are reviewed and discussed. Abstract : Electroactive ion exchange materials (EIXMs) with unique electrochemically switched ion exchange function have been extensively applied in various fields including high value-added ion recovery, toxic ion removal, energy storage devices and electrochemical ion sensors. In particular, the charge and discharge of EIXMs can be electrochemically controlled by an external electric field or by a redox agent while the charge balance is compensated via the ion exchange with electrolyte solution. To date, the discovered EIXMs mainly involve inorganic compounds with mixed-valence transition metals, organic conducting polymers and organic–inorganic hybrid materials. Compared with their bulk forms, nanostructured EIXMs have aroused considerable research interest recently owing to their unique properties such as larger surface area, better ion diffusion path and excellent electron transfer property. In this article, the design principles and synthetic routes for the development of various nanostructured EIXMs and their applications in the fields of selective ion separation, supercapacitors and electrochemical ion sensors are reviewed. In addition, the main challenges and future prospects for the further development of high-performance EIXMs are discussed.